Mechanisms underlying the antidepressant response and treatment resistance - Levinstein, Marjorie R.; Samuels, Benjamin A. (Frontiers in Behavioral Neuroscience, 2014)
Depression is a complex and heterogeneous disorder affecting millions of Americans. There are several different medications and other treatments that are available and effective for many patients with depression. However, a substantial percentage of patients fail to achieve remission with these currently available interventions, and relapse rates are high. Therefore, it is necessary to determine both the mechanisms underlying the antidepressant response and the differences between responders and non-responders to treatment. Delineation of these mechanisms largely relies on experiments that utilize animal models. Therefore, this review provides an overview of the various mouse models that are currently used to assess the antidepressant response, such as chronic mild stress, social defeat, and chronic corticosterone. We discuss how these mouse models can be used to advance our understanding of the differences between responders and non-responders to antidepressant treatment. We also provide an overview of experimental treatment modalities that are used for treatment-resistant depression, such as deep brain stimulation and ketamine administration. We will then review the various genetic polymorphisms and transgenic mice that display resistance to antidepressant treatment. Finally, we synthesize the published data to describe a potential neural circuit underlying the antidepressant response and treatment resistance.